2011
DOI: 10.1186/1479-5868-8-1
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of self-reported physical activity instruments in young people for population surveillance: Project ALPHA

Abstract: BackgroundThe assessment of physical activity is an essential part of understanding patterns and influences of behaviour, designing interventions, and undertaking population surveillance and monitoring, but it is particularly problematic when using self-report instruments with young people. This study reviewed available self-report physical activity instruments developed for use with children and adolescents to assess their suitability and feasibility for use in population surveillance systems, particularly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
386
2
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(406 citation statements)
references
References 30 publications
(19 reference statements)
11
386
2
7
Order By: Relevance
“…Responses were in a range from 0 days to 7 days, and according to the WHO recommendation (25) were classified into three categories as follows: 1 -active less than 2 days; 2 -active at least 3 days; 3 -active every day. Regarding to validity, authors concluded that moderate to vigorous physical activity (MVPA) index has acceptable validity for measuring amount of physical activity in adolescents (26)(27)(28).…”
Section: Methodsmentioning
confidence: 99%
“…Responses were in a range from 0 days to 7 days, and according to the WHO recommendation (25) were classified into three categories as follows: 1 -active less than 2 days; 2 -active at least 3 days; 3 -active every day. Regarding to validity, authors concluded that moderate to vigorous physical activity (MVPA) index has acceptable validity for measuring amount of physical activity in adolescents (26)(27)(28).…”
Section: Methodsmentioning
confidence: 99%
“…Results reported here may not generalizable to other geographic and cultural settings. Although self-reported data on PA may lead to misclassifi cation bias, self-report is a common and convenient strategy (Biddle, Gorely, Pearson, & Bull, 2011) and a validated questionnaire was used. Knowledge, attitudes, and competence in PA advising and personal PA habits may be diff erent for medical students at later stages of medical training and aft er exposure to more specifi c PA-related curricula.…”
Section: Study Limitationsmentioning
confidence: 99%
“…The Physical Activity Questionnaire for children and adolescents (PAQ-C & PAQ-A) are a cost-effective tools to assess PA patterns during childhood and adolescence (8) and they have been widely used in research and field settings. However, a limitation is that the outcome score is not readily interpretable (9). The PAQ asks for frequency spent in physical activities, which is a subjective rating of intensity, moreover their items are scored using ordinal scales (1-5 scale) and the outcome measure is computed as a simple mean of the individual items.…”
Section: Introductionmentioning
confidence: 99%